STUDI ANALISIS EIGENFACE DAN EIGEN FUZZY SET UNTUK EKSTRAKSI CIRI BIBIR PADA SISTEM IDENTIFIKASI WAJAH - M. Rahmat Widyanto; Shinta Puspasari (JUTI: Jurnal Ilmiah Teknologi Informasi, 2008)
This paper compares the performance of eigenface and eigen fuzzy set to extract lip traits. Testing is conducted by implementing the two methods in a face identification system based on lip traits. The database used is primary data that consists of front-face image and lip image. The test result shows that eigenface is more effective with average precisionrecall value 0.22% higher. However, statistical tests show that there are no significant differences between the two methods. An optimal extraction method will be used to develop face identification system based on facial components.